Research into the prevention and rehabilitation of dysphagia in head and neck cancer: a UK perspective. Issue 3 (June 2016) - Patterson, Joanne M.; Brady, Grainne C.; Roe, Justin W.G.
Abstract : Purpose of review: There is an increasing recognition of dysphagia as a frequent, often severe and chronic side-effect of head and neck cancer treatment. There has been a global increase in the number of head and neck cancer survivors, increasing the urgency of finding ways to best manage swallowing difficulties. Recent findings: There are several research studies investigating strategies and developing interventions to prevent and treat this debilitating condition. The United Kingdom has a growing number of trials and feasibility studies in this area, which have secured national funding. Research themes include changes, modifications, and de-escalation of cancer treatments to reduce side-effects; interventions to encourage maintenance of eating and drinking and swallowing exercises during radiotherapy; and novel interventions to address post-treatment dysphagia. Research into this field presents with numerous challenges, including issues with recruitment, retention, and adherence to rehabilitation programmes. Summary: In this study, we present recent advances in knowledge, research themes, and current UK-based research. Our multicentre studies will facilitate standardization of outcome measures and strengthen multidisciplinary, academic, and international collaborations. Findings over the coming years will help progress our understanding of how best to prevent and manage dysphagia in head and neck cancer.